Effect of cations on consolidation and permeability of polymerized bentonite - N. Prongmanee; J.C. Chai; S. Shrestha (International Association of Lowland Technology, 2018)
Properties of a novel material “polymerized bentonite (PB)” and a traditional untreated bentonite (UB) were investigated through two series of laboratory tests (i.e., consolidation test and filter press test). Three different test liquids included of deionized water, 0.6 M NaCl and 0.6 M CaCl2 were used in this study. The results of consolidation tests indicated that the compression index (Cc) and swelling index (Cs) decreased, while the coefficient of consolidation (cv) increased with the increasing in concentration and valence of cation in the solutions. Comparison between two materials in the cationic solutions, the PB had higher Cc and Cs value, but it gave lower cv value compared with that of the UB. The results of estimated permeability (kfilter) from the test results of the filter press showed that the PB gave lower values of kfilter for all the test solutions compared with those of the corresponding UB due to the polymer “locked” Na+ ions carried by the bentonite particles and partially prevented it to be replaced by higher cation charge. Based on the results of permeability, it is suggested that the PB can provide better barrier properties against aggressive cationic solutions compared to that of the UB.